Imaginative inventions : the who, what, where, when, and why of roller skates, potato chips, marbles, and pie and more! - Harper, Charise Mericle (Boston : Little Brown, 2001)
Tells the story behind the invention of many common things such as potato chips, chewing gum, and grocery bags.
"Megan Tingley books."
School Library Journal
Pub Weekly
Booklist
3.7
K-3
Keywords: Inventions -- History -- Juvenile literature; Inventions -- History; Inventions -- History